Storytelling and improvisation as anti-racist pedagogies challenging white supremacy in elementary education - Tanner, Samuel Jaye; Miller, Erin T. (New York : Routledge, 2024)
This book theorizes and describes the concept of transformative critical whiteness pedagogies that are rooted in theories and practices of improvisation. It shows how these pedagogies invite people, especially white people, into the urgent work of resisting the ongoing production and affirmation of white supremacy. Using the frameworks of storytelling and story analysis, this book uses narrative to invite the reader into ongoing work to design and make sense of teaching and learning about whiteness that would meaningfully account for a grapple with white supremacy. Chapter 1 offers the conceptual framework rooted in theories and practices of improvisation that allow for new ways to think about engaging whiteness in anti-racist pedagogies, which the authors name transformative critical whiteness pedagogies. Chapters 2-4 tell and analyze the stories that emerged out of this work to design and facilitate transformative critical whiteness pedagogies with white elementary students, white college students, and then black elementary students in the US. Chapters 5 and 6 discuss the challenges of developing and implementing transformative critical whiteness pedagogies in K-12 contexts. The final chapters offer a discussion of the improvisational ethos, as well as an overview of the authors' ongoing work to engage people, especially white people, in getting smarter about whiteness. Using simple, straightforward language to address complex ideas about anti-racist pedagogies, this volume will be important reading for pre-service teachers and teacher educators in Critical Whiteness Studies, Critical Multicultural Education, Social Foundations of Education, Elementary Education, and Race and Culture Studies.
Keywords: Storytelling in education -- United States; Storytelling -- Study and teaching (Elementary) -- United States; Improvisation (Acting); Racism in education -- United States; Race awareness -- Study and teaching (Elementary) -- United States; White people -- Race identity -- Study and teaching (Elementary) -- United States; Culturally relevant pedagogy -- United States; Critical pedagogy -- United States; Narrative inquiry (Research method); EDUCATION / General; EDUCATION / Multicultural Education; EDUCATION / Elementary